The impact of investing social security funds on the sustainability of insurance funds (A study of the experiences of some Arab countries from 2013-2022) - Al-Sharafi, Sanaa Taysir (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to identify the impact of investing the surplus funds of social security corporations on the sustainability and continuity of insurance funds in covering their insurance commitments to their beneficiaries. The study shows the types of financing for insurance funds, whether it is total financing, partial financing, or annual financing, and presents the concept of the investment fund for the social security corporation and its objectives, determinants of investment and risk management, and the best practices used to ensure a feasible financial return from investment, which contributes to ensuring the cash flow to pay the financial commitments of the insurance funds. The researcher used the inductive and comparative approach, as the study reviews a comparison between the Investment Fund of the Jordanian Social Security Corporation and the Investment Authority Of Social Security Corporation of Oman, and the impact of following appropriate policies, good practices, and governance in increasing the return on investment which raises and progresses the insurance benefits granted to beneficiaries of insurance funds, and increases the hedge of each fund to face any changes in demographics or emergency economic crises. The research reached its results as Investment funds that follow clear policies represented in low-risk investment methods and conducted the necessary studies and followed best practices and the separation of duties were the most successful in managing the capital of insurance funds, The investment is sufficient to meet the responsibilities of the insurance funds. The researcher recommended the importance of establishing an independent investment fund to manage the funds of the Palestinian Social Security Corporation upon its establishment and to exchange practical experiences with neighboring countries.